Oncology distress screening within predominately Black Veterans: Outcomes on supportive care utilization, hospitalizations, and mortality. (27th December 2022) - Azizoddin, Desiree R.; Allsop, Matthew; Farah, Subrina; Salim, Farah; Hauser, Joshua; Baltazar, Ashton R.; Molokie, Robert; Weber, Jane; Weldon, Christine; Feldman, Lawrence; Martin, Joanna L.
Abstract: Background: We evaluated whether patients' initial screening symptoms were related to subsequent utilization of supportive care services and hospitalizations, and whether patient‐level demographics, symptoms, hospitalizations, and supportive care service utilization were associated with mortality in primarily low‐income, older, Black Veterans with cancer. Methods: This quality improvement project created collaborative clinics to conduct cancer distress screenings and refer to supportive care services at an urban, VA medical center. All patients completed a distress screen with follow‐up screening every 3 months. Supportive care utilization, hospitalization rates, and mortality were abstracted through medical records. Poisson regression models and cox proportional hazard models were utilized. Results: Five hundred and eighty five screened patients were older ( m = 72), mostly Black 70% ( n = 412), and had advanced cancer 54%. Fifty‐eight percent ( n = 340) were screened only once with 81% ( n = 470) receiving ≥1 supportive care service and 51.5% ( n = 297) being hospitalized ≥1 time 18 months following initial screen. Symptom severity was significantly related to number of hospitalizations. Low mood was significantly related to higher supportive services ( p < 0.001), but not hospitalizations ( p ≥ 0.52). Pain, fatigue, physical function, nutrition, and physical symptoms were significantly associated with more supportive services and hospitalizations ( p < 0.01). Twenty percent ( n = 168) died; Veterans who were Black, had lower stage cancers, better physical health, and utilized less supportive care services had lower odds of mortality ( p ≤ 0.01). Conclusion: Individuals with elevated distress needs and those reporting lower physical function utilized more supportive care services and had higher hospitalization rates. Lower physical function, greater supportive care use, higher stage cancer, and being non‐Black were associated with higher odds of death.